Light stimulation on tenocytes: A systematic review of in vitro studies - Silva, Mariana Isabel Santos Rodrigues (2022)
Background: The purpose of this systematic review is to analyze the methodologies, utilized stimulation parameters, and the main cellular outcomes obtained by in vitro studies that apply a light source on tenocyte cultures. Methods: The PubMed, Scopus, and Web of Science databases were searched up to December 9, 2019 for in vitro studies that used light sources on tenocyte cultures. A 13-item checklist was used to assess methodological quality of the studies and the risk of bias was assessed using the Risk of Bias Assessment tool for Non-randomized Studies tool. Results: Six studies were included. Tenocytes from the Achilles tendon were used by 83.3% of the studies, with 16.7% utilizing the deep digital flexor tendon, with cells in passage 2 to 5. Four studies used lasers and the other 2 used light-emitting diode or intense pulsed light, in wavelengths ranges from 530 to 1100 nm. The application of light to tenocytes resulted in positive effects reported by all studies, including an increase in cell proliferation and migration, and higher protein and gene expression of tendon biomarkers. Studies presented a lack of standardization on reporting light stimulation parameters and experimental methodologies, leading to low methodological quality. There was a high risk of selection, performance, detection, and reporting bias. Conclusions: All studies showed positive effects after light stimulation on tenocytes, regardless of the light source used. However, the lack of standardized data on light stimulation parameters, experimental setup, and the studies’ main limitations hindered representative conclusions and comparisons amongst studies’ main outcomes.